Composite Fabrication on Age-Hardened Alloy Using Friction Stir Processing - Gangil, Namrata; Siddiquee, Arshad Noor; Maheshwari, Sachin (Boca Raton, FL : CRC Press, 2021)
This up-to-date reference text discusses the fabrication technique for strengthening of high specific strength alloys including age-hardened aluminum alloys for several industrial applications. The text presents an exhaustive overview of the materials used in the aircraft construction in general and age-hardened aluminum alloys in particular. The text discusses important concepts including surface composite fabrication using friction stir processing (FSP), FSP tools, effect of reinforcement particles, and conditions that affect strengthening during surface composite fabrication on age-hardened aluminum alloys. The text will facilitate the readers to control parameters and avoid conditions that lead to a net negative impact on the resulting composites and select the one that lead to a net gain. It will enable the readers, researchers, and professionals to plan and practice composite fabrication via FSP with a benefit of net strengthening. The understanding of specific strength of materials used in applications including aerial vehicles and manufacturing is important. The proposed text highlights importance of age-hardened alloy as one of the materials used for diverse applications. It discusses strengthening strategies of existing age-hardened aluminum alloys through composite fabrication via a solid-state FSP route. The text will help students and professionals working in the field of manufacturing, materials science, and aerospace engineering. The text discusses an important aspect of strengthening age-hardened alloy using solid-state friction stir processing for diverse applications in industries including manufacturing and aviation. It will serve as an ideal reference for graduate students, academic researchers, and professionals in the field of mechanical engineering, aerospace engineering, and materials science. It will also be helpful to the professionals working in the aviation and manufacturing industries.
OCLC-licensed vendor bibliographic record.
Keywords: Alloys; Friction stir welding; Strength of materials; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Manufacturing; TECHNOLOGY / Nanotechnology